AN ANALYSIS ON STUDENTS’ ERRORS IN USING PREPOSITION AT THIRD GRADE OF SMP NEGERI 1 PANYABUNGAN UTARA MANDAILING NATAL SUMATERA UTARA - Hanapi, Ahmad (Faculty of Tarbiyah nad Teacher Training, 2023)
The study aims to realize students’ understanding and ability in using the prepositions of time and place. The research was conducted using both qualitative and quantitative methods. The subjects of this study were students of class 3A of SMP Negeri 1 Panyabungan Utara Mandailing Natal for the 2020/2021 academic year. In this study, researcher used qualitative and quantitative descriptive approach, the researcher recognized the errors and explained them. The qualitative data were taken from interviews, observation, documentation while the quantitative data were taken from a test containing the use of the prepositions of time and place from 20 students. The second step is identifying the errors based on the outside of the test range tested, and the third step is describing the errors made by students. The results showed that there were 212 students who get errors from 400 questions in using time and place preposition. Researchers found that some errors that occur due to misinformation. Another finding is that the source of the error is divided in two categories, namely overgeneralization (the effect of the previous rules/formulas) and ignorance of role limitations (the effect of failure to apply the rule formula). And based on the interviews, observations, sheets and documentation, it showed that students’ responses in using prepositions are not good enough.